Metal-organic framework glasses with permanent accessible porosity - Zhou, Chao (Nat Commun, 2018)
To date, only several microporous, and even fewer nanoporous, glasses have been produced, always via post synthesis acid treatment of phase separated dense materials, e.g. Vycor glass. In contrast, high internal surface areas are readily achieved in crystalline materials, such as metal-organic frameworks (MOFs). It has recently been discovered that a new family of melt quenched glasses can be produced from MOFs, though they have thus far lacked the accessible and intrinsic porosity of their crystalline precursors. Here, we report the first glasses that are permanently and reversibly porous toward incoming gases, without post-synthetic treatment. We characterize the structure of these glasses using a range of experimental techniques, and demonstrate pores in the range of 4 – 8 Å. The discovery of MOF glasses with permanent accessible porosity reveals a new category of porous glass materials that are elevated beyond conventional inorganic and organic porous glasses by their diversity and tunability.